3D printed‐polylactic acid scaffolds coated with natural rubber latex for biomedical application. Issue 9 (1st October 2021) - Marcatto, Vinicius Assis; Sant'Ana Pegorin, Giovana; Barbosa, Gustavo Franco; Herculano, Rondinelli Donizetti; Guerra, Nayrim Brizuela
Abstract: Three‐dimensional (3D) printing is a rapidly growing technology and plays an emerging role in several biomedical applications. Polylactic acid (PLA) is one of the most common materials in 3D printing, however, it is chemically inert due to the absence of reactive side chain groups. In this context, in this work, the PLA scaffolds with two different geometries were produced and coated with natural rubber latex (NRL) extracted from the rubber tree Hevea brasiliensis . NRL presents bioactive substances that are related to its biological properties. The results revealed scaffolds with interconnected pores and pores sizes from 600 to 1300 μm. The NRL coatings caused a decrease in pore size. Infrared spectra showed that 2 NRL layers were more efficient in coverage. Compressive strength values obtained are in agreement with the spongy bones value (22–24 MPa for crossbar and 20–22 MPa for roundbar cube). Finally, the hemolytic activity of the PLA scaffold was 3%, while the scaffolds coated with 1 and 2 NRL layers presented values of 0%, indicating a potential use in biomedical applications due to the absence of hemolytic effects. Abstract :